Healthcare workers’ perspectives on Ayushman Bharat Yojana in Kashmir: Insights for policy and practice - Shahroz Nabi; Taha Ayub; S. Muhammad S. Khan; Mohammad Iqbal Pandit; Inaamul Haq; Mariya Amin Qurieshi (Journal of Family Medicine and Primary Care, 2024)
Background: In India, the Ayushman Bharat Program aims to provide comprehensive healthcare coverage to underprivileged communities, guided by the 2017 National Health Policy and aligned with Sustainable Development Goals. This study explores healthcare workers’ perspectives on the implementation, impact, and challenges of Ayushman Bharat Yojana (ABY) in Kashmir, focusing on primary care services. Methods: A mixed-methods study was conducted over ten months (October 2020 to August 2021) across ten districts in Kashmir. Fifty healthcare professionals, including 30 mid-level healthcare providers (MLHPs) and 20 medical officers, participated in semi-structured interviews and completed structured questionnaires. Data were analyzed using thematic analysis for qualitative data and descriptive statistics for quantitative data. Results: Demographics: Among the respondents, 64% were under 30 years, and 56% were female. Positions included 40% medical officers and 60% MLHPs. Qualitative Findings: Both MLHPs and medical officers had varying levels of awareness about ABY. Key challenges included inadequate infrastructure, staffing shortages, additional duties, and long commutes. Effective communication and collaboration between MLHPs and medical officers were deemed crucial for successful implementation. Ongoing training and support were highlighted as essential needs. Quantitative Findings: Significant issues included irregular payments (66.6% MLHPs reported receiving regular incentives), staffing shortages (50% medical officers), and lack of training (35% medical officers). Common ailments managed included hypertension (33.33%) and infections (26.66%). Conclusion: The study highlights the challenges and insights from healthcare workers regarding the ABY program in Kashmir. Addressing infrastructure deficiencies, improving communication, and providing ongoing training and financial stability are essential for enhancing the program’s effectiveness. Policymakers must consider these findings to improve healthcare delivery and ensure the sustained success of the Ayushman Bharat initiative.